Fine Needle Aspiration Cytology of Primary and Secondary Testicular Lymphoma and its Clinical Mimickers- A Definite Indication - Gochhait, Debasis; Kekade, Shailesh; Rekha, Jinkala Sree; Badhe, Bhawana Ashok (Annals of Pathology and Laboratory Medicine, 2021)
Albeit being rare, the testicular lymphoma is the most common testicular malignancy in elders. In early stages, its symptoms are non-specific and can mimic other underlying diseases. The available knowledge of cytology on this entity is not adequate. In case when a clinician comes across a testicular enlargement case, a decision has to be made when to send the patient for FNAC. Similarly, the pathologist who is assessing the patient should also make a decision whether to perform Fine Needle Aspiration Cytology (FNAC) on the patient or not, and what morphology is expected on cytological smears to be able to confidently call it testicular lymphoma. We have undertaken this study to serve the purpose of enhancing the sparse knowledge available on this disease, dealt with its multiorgan involvement, and explained how FNAC is a valuable utility in testicular enlargement cases in which serological markers of testicular malignancy are negative.